Does success breed success? An investigation of momentum in elite recurve archery - Zhao, Y.; Zhang, H. (Psychology of Sport and Exercise, 2023)
We investigate the existence of momentum or the "hot hand" phenomenon in recurve archery, in which archers have three shots per set. We collected the performance of archers along with the control variable (player difference) and game data (set score difference, shooting order and game type). We set out to compare the outcome (bullseye, 10 points, probability) and performance (scores of the third shot) in a range of cases with the previous two shots. The most obvious finding to emerge from this study is the powerful evidence for positive momentum in recurve archery. The key finding that hitting the bullseye creates momentum and momentum leads to better performance has been confirmed as the "success breeds success" mechanism. Furthermore, the performance of the third shot is influenced by competitive ability and match importance (Olympic Games or not).